The Efficiency of the Educaplay-Assisted PBL in Improving Student Learning Outcomes in Physics - Ni Putu Anindita Dara Maheswari; Marshanda V. Menajang; Dyta Puspita Ningrum; Riziqul Ikram (Yayasan Siti Widhatul Faeha Salahudin Syawal, 2025)
The low physics learning outcomes at SMAN 2 Mataram encourage the need to apply innovative technology-based learning models. The purpose of this study is to evaluate the efficacy of Problem-Based Learning (PBL) assisted by the Educaplay platform in enhancing physics learning outcomes for the Dynamic Fluids material. Using a quasi-experimental design with purposive sampling of 54 students (33 in the experimental class and 21 in the control class), this study analyzed data through N-Gain tests and observations of the affective-psychomotor domain. The results showed significant improvements in the experimental class, with high N-Gain scores in the cognitive domains C1 (0.92) and C3 (0.70), as well as superior improvements in the affective (97%) and psychomotor (95%) domains compared to the control class. These findings demonstrate that integrating PBL and Educaplay can create an interactive and holistic learning environment. The study recommends implementing this model as an alternative approach to physics education, emphasizing the importance of technical support for students, while also contributing empirical evidence to the development of digital-based learning theories in the educational context.